2021
DOI: 10.3390/foods10112639
|View full text |Cite
|
Sign up to set email alerts
|

Eating Fermented: Health Benefits of LAB-Fermented Foods

Abstract: Lactic acid bacteria (LAB) are involved in producing a considerable number of fermented products consumed worldwide. Many of those LAB fermented foods are recognized as beneficial for human health due to probiotic LAB or their metabolites produced during food fermentation or after food digestion. In this review, we aim to gather and discuss available information on the health-related effects of LAB-fermented foods. In particular, we focused on the most widely consumed LAB-fermented foods such as yoghurt, kefir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 124 publications
(156 reference statements)
0
57
0
7
Order By: Relevance
“…At present, fermented food plays an important role in human diets due to its special taste and unique aroma ( Marco et al, 2021 ; Soto-Giron et al, 2021 ). In addition, the health-related properties of fermented food significantly promote their consumption around the world ( Castellone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, fermented food plays an important role in human diets due to its special taste and unique aroma ( Marco et al, 2021 ; Soto-Giron et al, 2021 ). In addition, the health-related properties of fermented food significantly promote their consumption around the world ( Castellone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most essential and frequently used microorganisms in food fermentation processes are different species of bacteria, yeasts, and filamentous fungi [ 10 , 11 ]. Among bacteria, lactic acid bacteria (LAB), mostly Lactobacillus , Lactococcus, and Tetragenococcus, are widely present in many fermented foods, especially fermented milk and soy products [ 10 , 12 ]. Apart from LAB, certain species of acetic acid bacteria (AAB) are associated with fermentation processes of vinegar and kombucha or support meat and cheese fermentation, as in the cases of Staphylococcus , Enterococcus , Brevibacterium, and Propionibacterium [ 8 , 10 , 13 ].…”
Section: Types Of Fermented Foodsmentioning
confidence: 99%
“…Yogurt, kefir, and other fermented dairy products represent one of the most attractive sources of probiotic strains, mainly Lactobacillus spp. and S. thermophiles , as it has been shown that cultured dairy products consistently contained the highest levels of LAB [ 5 , 12 , 16 , 20 , 24 ]. However, probiotic strains such as Lactobacillus plantarum and Lactobacillus rhamnosus are also incorporated in oat-based fermented beverages that also contain the prebiotic fiber β–glucan [ 25 ].…”
Section: Health-promoting Components In Fermented Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional fermented foods were potential sources of probiotics as they were often composed mainly of lactic acid bacteria (LAB), including Lactobacillus , Pediococcus , Enterococcus , Weisella, and Leuconostoc [ 4 ]. In fermented foods, LAB produces copious amounts of metabolites such as lactic acid, acetic acid, ethanol, carbon dioxide, fatty acids, and antimicrobial peptides, which are responsible for flavor, texture, and preservation [ 19 , 20 , 21 ]. Furthermore, LAB could release kinds of bioactive compounds to improve the nutritive values of fermented foods.…”
Section: Introductionmentioning
confidence: 99%